2013
DOI: 10.1589/jpts.25.159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Wrist Motion Storage Biofeedback System (WMSBS) on Wrist Motion during Keyboard Typing Work

Abstract: Abstract.[Purpose] The purpose of this study was to examine the effect of a wrist motion storage biofeedback system on wrist range of motion during keyboard typing work.[Subjects] For this study, we recruited 10 computer workers as volunteers.[Methods] Wrist flexion, extension, ulnar deviation, and radial deviation angles were analyzed using a 3-D motion analysis system. [Results] The wrist flexion, extension, ulnar deviation, and radial deviation angles decreased significantly in keyboard typing work with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Recently, many studies have suggested the use of therapeutic or exercise tools with biofeedback, which provides additional information about users by detecting subtle changes in the body with sensors 1 , 2 , 3 ) . Many therapists give visual and auditory feedback, even during clinical trials 4 ) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, many studies have suggested the use of therapeutic or exercise tools with biofeedback, which provides additional information about users by detecting subtle changes in the body with sensors 1 , 2 , 3 ) . Many therapists give visual and auditory feedback, even during clinical trials 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there is active research being conducted on the development of a biofeedback tool for people who work at a computer for long hours while sitting in a bad posture 1 , 2 , 3 ) . Researchers have been boosting the sensor capacity of biofeedback tools in order to improve the effectiveness of posture exercises and other exercises 1 , 2 , 3 ) . Such improvement in the tools offers quick feedback of subtle changes in the body 4 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical treatment for CTS involves opening the carpal tunnel at the wrist. Currently, there are several non-surgical treatments for CTS, including non-steroidal anti-inflammatory drugs, injection of various medications, immobilization by splinting, rehabilitation modalities, and biofeedback devices 5 , 6 ) . While drugs, injections, and splinting relieve the symptoms of CTS, the long-term outcomes are poor 1 ) .…”
Section: Introductionmentioning
confidence: 99%